KARAKTERISASI ASAP CAIR HASIL PIROLISIS SAMPAH ORGANIK PADAT (CHARACTERIZATION OF LIQUID SMOKE PYROLYZED FROM SOLID ORGANIC WASTE) - Abdul Gani Haji, Zainal Alim Mas’ud, Bibiana W. Lay, Surjono H. Sutjahjo dan Gustan Pari (Department of Agroindustrial Technology, Bogor Agricultural University, 2006)
AbstractThe liquid smoke had been produced from raw material of solid organic waste using pyrolysis reactor. The composition of organic waste as 30% bamboo, 30% wood, 20% small branch and 20% fruit peel was separated and coped manually, and then put into pyrolysis reactor. Pyrolysing processing at 350-510 oC for 5 hours and liquid smoke produced was characterized by means of rendement, total phenol and pH parameter. Besides that, the liquid smoke component was identified by GCMS. The result of this research showed that the liquid smoke was generally brownish-red color, with rendement 22.87-34.67 %, pH 3.8-4.8, and total phenolic 6.15x10-3-2.24x10-2 %. Increasing pyrolysis temperature up to 505 oC tended to increase total phenolic compound. GCMS analysis on the liquid smoke identified 61 compound, i.e. ketone (17 compounds), phenolic (14 compounds), carboxylic acid (8 compounds), alcohols (7 compounds), ester (4 compounds), aldehyde (3 compounds), and other 1 compounds. Keywords: liquid smoke, solid organic waste, pyrolysis, quality